Should African Monetary Unions Be Expanded? An Empirical Investigation of the Scope for Monetary Integration in Sub-Saharan Africa - Debrun, Xavier (International Monetary Fund, 2010)
This paper develops a full-fledged cost-benefit analysis of monetary integration, and applies it to the currency unions actively pursued in Africa. The benefits of monetary union come from a more credible monetary policy, while the costs derive from real shock asymmetries and fiscal disparities. The model is calibrated using African data. Simulations indicate that the proposed EAC, ECOWAS, and SADC monetary unions bring about net benefits to some potential members, but modest net gains and sometimes net losses for others. Strengthening domestic macroeconomic frameworks is shown to provide some of the same improvements as monetary integration, reducing the latter's relative attractiveness